Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/molecules25215064
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiviral Activity of Doxycycline against SARS-CoV-2

Abstract: In December 2019, a new severe acute respiratory syndrome coronavirus (SARS-CoV-2), causing coronavirus disease 2019 (COVID-19), emerged in Wuhan, China. Despite containment measures, SARS-CoV-2 spread in Asia, Southern Europe, then in America and currently in Africa. Identifying effective antiviral drugs is urgently needed. An efficient approach to drug discovery is to evaluate whether existing approved drugs can be efficient against SARS-CoV-2. Doxycycline, which is a second-generation tetracycline with broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 64 publications
(80 reference statements)
4
65
3
2
Order By: Relevance
“…The above two computational studies pointed toward potential antiviral (against SARS-CoV-2) effect of tetracyclines. Gendrot et al demonstrated in vitro activity of doxycycline in SARS-CoV-2 infected Vero E6 cells with median effective concentrations of 4.5 µM that seems to be compatible with oral as well as intravenous routes of administration [ 85 ].…”
Section: Tetracyclines: Potential In Covid-19 Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The above two computational studies pointed toward potential antiviral (against SARS-CoV-2) effect of tetracyclines. Gendrot et al demonstrated in vitro activity of doxycycline in SARS-CoV-2 infected Vero E6 cells with median effective concentrations of 4.5 µM that seems to be compatible with oral as well as intravenous routes of administration [ 85 ].…”
Section: Tetracyclines: Potential In Covid-19 Managementmentioning
confidence: 99%
“…As a result, use of dexamethasone has been encouraged for the management of COVID-19. Similarly, tetracyclines (doxycycline and minocycline) have also shown encouraging results in in silico [ 83 , 84 ], in vitro [ 85 ], and small sized clinical studies [ 86–93 ]. Long-term use of GCs can cause several adverse effects [ 31 ], but as severe COVID-19 is primary a life-threatening acute infection, dexamethasone is likely to be used for a shorter duration.…”
Section: Benefits and Drawbacks Of Concomitant Use Of Dexamethasone Amentioning
confidence: 99%
“…EXPT00713 (DB03648) is a P. falciparum formylmethionine deformylase inhibitor with a reported IC 50 of 130 nM . Interestingly, several antimalarial drugs are under the spotlight of COVID-19 investigations (Gendrot et al, 2020).…”
Section: Candidates For Drug Repurposingmentioning
confidence: 99%
“…For example, Fredeking et al [ 18 ] illustrated that doxycycline reduces pro-inflammatory cytokines in patients with dengue hemorrhagic fever. Furthermore, different reports disclosed the potential benefit of doxycycline therapy in the management of COVID-19 due to its anti-inflammatory and anti-SARS-CoV-2 activities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%